1990
DOI: 10.1002/1097-0142(19901215)66:12<2645::aid-cncr2820661230>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Dentofacial development in long-term survivors of acute lymphoblastic leukemia: A comparison of three treatment modalities

Abstract: Ninety-seven children who were diagnosed with acute lymphoblastic leukemia before 10 years of age and treated with chemotherapy alone, chemotherapy plus 1800-cGy cranial irradiation (RT), or chemotherapy plus 2400-cGy RT were evaluated for effects of therapy on dentofacial development. All patients were seen at least 5 years postdiagnosis. Dental abnormalities were determined from panoramic radiographs, and craniofacial evaluations were made from lateral cephalometric radiographs. Ninety-one (94%) of all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
131
3
17

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(165 citation statements)
references
References 23 publications
14
131
3
17
Order By: Relevance
“…These findings were consistent with previous studies. [5][6][7][8][9][10][11][12][13] Dental development is a complex and prolonged process. The development of permanent teeth is initiated between 5 months in utero and 9 months postnatally (excluding third molars), and the initial calcification process (excluding third molars) occurs between 3 months and 3 years of age and continues until coronal development is complete around 8 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with previous studies. [5][6][7][8][9][10][11][12][13] Dental development is a complex and prolonged process. The development of permanent teeth is initiated between 5 months in utero and 9 months postnatally (excluding third molars), and the initial calcification process (excluding third molars) occurs between 3 months and 3 years of age and continues until coronal development is complete around 8 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…1 Well-established long-term effects of antineoplastic treatment include dental disturbances such as microdontia, 2 atypical root formation, 3,4 and tooth aplasia. [5][6][7][8][9][10][11][12][13][14] Other effects include hyposalivation, [15][16][17] dental immaturity and disturbances in dental eruption, as well as trismus and osteoradionecrosis. 18 However, it is difficult to attribute these effects to any single agent or treatment modality, as multimodal therapy is employed in almost all childhood cancers.…”
mentioning
confidence: 99%
“…6,7 In these conditions, the root dysplasia is generalized or affects a continuous section of a dental arch. Premature arrest of radicular development results from local events such as traumas, infections, or radiation therapy, systemic influences like chemotherapy, [8][9][10] and sometimes without any apparent reason. 11 Therefore, this type of dysplasia usually affects individual teeth or a specific group of teeth, roots of which form at the time of the external insult.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that HERS cells are sensitive to vinblastine at/near commonly used pharmacologic doses, and adds support to clinical findings that abnormal root morphology in childhood cancer survivors is the result of damage to HERS cells proliferating at the time of chemotherapy. [1][2][3][4][5][6][7] There was a beneficial effect of photobiomodulation on HERS cell recovery from vinblastine exposure. The greatest effects of the light treatment were noted at the LD 50 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Numerous studies of the long-term effects of chemotherapy on dental development have found that the most common abnormality is atypical root morphology. [2][3][4][5][6][7] Hertwig's epithelial root sheath (HERS) cells are considered to be the cells responsible for root formation. The apical migration of these cells during root development determines the eventual morphology of the root.…”
Section: Introductionmentioning
confidence: 99%